ANALISIS TOTAL COLIFORM PADA SUSU KEDELAI USAHA KECIL MENENGAH DI KOTA PADANG - Shinta - Silvia (Fakultas Teknik Universitas Riau, 2021)
Beverage production can be contaminated with pathogenic bacteria due to unhygienic processing. Bacteriological conditions can be determined from the presence of Total Coliform. This study aims to examine the Total Coliform contained in soy milk drinks produced by Small and Medium Enterprises (SMEs) in the City of Padang. Tests were carried out on five soy milk processing places in Padang City with three times the frequency of sampling. Total Coliform is calculated using the Most Probable Number (MPN) Method. Total Coliform based on SNI 01-3830-1995 regarding Soybean Milk Quality Requirements is 20 MPN / ml. Analysis of the presence of Total Coliform in the five Small and Medium Enterprises in Padang City is as follows: 1.54 MPN / ml; 3.60 MPN / ml; 2.74 MPN / ml; 41.11 MPN / ml and 4.2 MPN / ml. The results showed that four out of five soybean milk businesses met the quality requirements. Keywords: Soybean Milk, Total Coliform, Small and Medium Enterprises, Padang City